A study of the mechanism of small-molecule soybean-protein-derived peptide supplement to promote sleep in a mouse model. Issue 19 (18th March 2020) - Yi, Guofu; Safdar, Bushra; Zhang, Yihao; Li, You; Liu, Xinqi
Abstract : Here, the effects of dietary supplementation with small-molecule soybean-protein-derived peptide (SBP) on sleep duration in mice are described. Abstract : Here, the effects of dietary supplementation with small-molecule soybean-protein-derived peptide (SBP) on sleep duration in mice are described. The amounts of the neurotransmitters tryptophan (Trp, W), 5-hydroxytryptamine (5-HTP), serotonin (5-HT) and melatonin (MT) were determined by using an ELISA kit. Compared with the control group, the group of mice given 0.65 g kg −1 SBP showed 59.21% prolonged sleep at the third day of administration and significantly increased MT levels, by 95.31%. Western blotting analysis of 0.65 g kg −1 SBP revealed the presence of tryptophan hydroxylase (THP) and serotonin- N -acetyltransferase (AANAT) proteins, which increased the release of MT and upregulated the MT1 and MT2 receptor activities to alleviate sleep deprivation. Interestingly, the introduction of 2.60 g kg −1 SBP doubled the 5-HT content in the brain and promoted an awake state. As a result, the produced 5-HT could not be converted into MT in large amounts, so the sleep duration was shorter than that of the control group. These findings suggested the potential of using SBP in appropriate amounts as functional ingredients in various food products to improve sleep in elderly people afflicted with sleep disorders.